The Interpretation of Verbal Probability Expressions Used in the IAS/IFRS: Some Portuguese Evidence - Teixeira,Cláudia (2009)
One of the main arguments in favour of the adoption and convergence with the international accounting standards published by the IASB (i.e. IAS/IFRS) is that these will allow comparability of financial reporting across countries. However, because these standards use verbal probability expressions (e.g. probable) they require professional accountants to interpret and classify the probability of an outcome or event taking into account those terms and expressions and to best decide in terms of financial reporting. This paper reports part of a research on the interpretation of verbal probability expressions used in the IAS/IFRS by the auditors registered with the Portuguese Securities Market Commission (CMVM). This analysis was made in isolation, that is, without considering a context. The findings show that these terms and expressions are differently perceived by the auditors. Thus the paper provides evidence that suggests that it is fair to review the use of verbal probability expressions in accounting standards, namely the IAS/IFRS.